Adaptive relaying protocol for wireless energy harvesting and information processing in NOMA systems: Outage probability analysis - Phu Tran Tin; Duy-Hung Ha; Tran Thanh Trang (Institute of Advanced Engineering and Science, 2020)
In order to satisfy the increasing data rate demands, the research in the fifth-generation (5G) wireless networks is ongoing, both in academia and industry. In this research, we propose and investigate adaptive relaying protocol (ARP) For wireless energy harvesting (EH) and information processing in NOMA systems. Firstly, we investigate and derive the closed-form and integral-form expressions of the outage probability (OP) of the model system. Then, all the results are convinced by the Monte Carlo simulation. The research results show that all the analytical and simulation results are the same in connection with the primary system parameters. This research can provide a recommendation for NOMA system network.